2009
DOI: 10.1111/j.1365-2621.2009.01926.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural preservative ingredient from marine alga Ulva lactuca L.

Abstract: The contents of total chlorophyll (T-Chl), carotenoids and phenolics compounds were quantified in the biomasses of Ulva lactuca grown either in normal or artificial sea water under indoor conditions. The antioxidant and antibacterial activities of U. lactuca crude organic extracts (Ulva-COEs) were determined. Thirty-four compounds in Ulva-COEs were characterised by thin layer chromatography and highperformance liquid chromatography. The major compounds were chlorophyll a (Chl a) (15.60-30.90%) and b (Chl b) (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 33 publications
4
18
0
7
Order By: Relevance
“…In agreement with this difference, a valuable polyphenol content (53.5 ± 5.0 mg GAE g −1 lyophilized alga) was measured in F. spiralis samples employed in the current study, while U. lactuca showed a markedly lower polyphenol content (0.7 ± 0.6 mg GAE g −1 lyophilized alga). However, previous research has reported on the antioxidant behaviour of U. lactuca , this activity being explained by the presence of preservative molecules such as tocopherols, carotenoids, phenolic compounds, and sulfates …”
Section: Resultsmentioning
confidence: 96%
“…In agreement with this difference, a valuable polyphenol content (53.5 ± 5.0 mg GAE g −1 lyophilized alga) was measured in F. spiralis samples employed in the current study, while U. lactuca showed a markedly lower polyphenol content (0.7 ± 0.6 mg GAE g −1 lyophilized alga). However, previous research has reported on the antioxidant behaviour of U. lactuca , this activity being explained by the presence of preservative molecules such as tocopherols, carotenoids, phenolic compounds, and sulfates …”
Section: Resultsmentioning
confidence: 96%
“…Thus, the potential antioxidant effect of the phenolic and nonenzymatic compounds of Ulva rigida (Abd El‐Baky et al. , Hassan and Ghareib , Fabrowska et al. , Messyasz et al.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in algae exposed to PAR treatment the maximum increase was 40%. Thus, the potential antioxidant effect of the phenolic and nonenzymatic compounds of Ulva rigida (Abd El-Baky et al 2009, Hassan and Ghareib 2009, Fabrowska et al 2016, Messyasz et al 2018) could be ruled out, due to its low activity, delayed increase (only after 16 h), and undifferentiated response to UV stress. In fact, there were no significant changes between treatments with and without the presence of UV radiation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the worldwide market value of all carotenoids was US$887 million in 2004 and reached US$1,023 million by the end of the decade (Del Campo et al, 2007). Many studies reported that carotenoids of Dunaliella are efficacious in preventing oxidative stress-related lung and liver pathologies due to scavenging of the reactive oxygen species, generated during pathological processes (Hughes, 1997;Raja et al, 2007;Abd El-Baky et al, 2009b). Therefore, the scavenging of oxygen free radicals ( 1 O 2 , .…”
Section: Introductionmentioning
confidence: 97%
“…The chemical composition of some microalgae indicates that it has a high nutritional value due to a wide range of essential nutrients-such as vitamins, minerals, and proteins (Sathivel et al, 2008;Abd El-Baky et al, 2006). Moreover, it contains a wide range of compounds that are used or could be potentially employed as functional ingredients including carotenoids, polyphenols and other antioxidant pigments, and omega (ω)-3 and ω-6 polyunsaturated fatty acids (Abd El-Baky et al, 2008, 2009b.…”
Section: Introductionmentioning
confidence: 99%